2021
DOI: 10.9734/jpri/2020/v32i4831128
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Metabolic Syndrome, Uric Acid and Leisure Time Physical Activity between Former Athletes and Non-Athlees

Abstract: This study aims to determine the prevalence of metabolic syndrome (MS), overweight and obesity, uric acid (UA), and leisure time physical activity (LTPA) among former athletes and non-athletes in the Kingdom of Saudi Arabia (KSA). Moreover, to determine the effects of previous high intensity training on MS risk factors, overweight and obesity, and UA. Seventy-five (75) former athletes and twenty-six (26) non-athletes, aged between 26 and 60 years old, participated in this study. Height, weight, waist circumfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Resistance and strength training have a positive influence on insulin resistance, stimulating the uptake of glucose by muscle cells [ 1 ]. Physical activity is considered very efficient regarding the effects on the metabolic profile of former athletes [ 2 ]. Physical exercise is also associated with many health-related benefits, reducing the risk of developing various chronic diseases, such as obesity, cardiovascular disease, and type II diabetes mellitus [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance and strength training have a positive influence on insulin resistance, stimulating the uptake of glucose by muscle cells [ 1 ]. Physical activity is considered very efficient regarding the effects on the metabolic profile of former athletes [ 2 ]. Physical exercise is also associated with many health-related benefits, reducing the risk of developing various chronic diseases, such as obesity, cardiovascular disease, and type II diabetes mellitus [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is has been reported that engaging in regular PA and exercise in early stages of life has a significant role in later life [3,5,6,9]. Participating in sports in early life can lower the prevalence of several noncommunicable diseases such as diabetes [10]. According to Batista and Soares [6], to be an athlete at a high level is often associated with the possibility of a decline in the appearance of several noncommunicable diseases.…”
Section: Introductionmentioning
confidence: 99%